Comparison of Two Major Perioperative Bleeding Scores for Cardiac Surgery Trials: Universal Definition of Perioperative Bleeding in Cardiac Surgery and European Coronary Artery Bypass Grafting Bleeding Severity Grade. (December 2018) - Bartoszko, Justyna; Wijeysundera, Duminda N.; Karkouti, Keyvan; Callum, Jeannie; Rao, Vivek; Crowther, Mark; Grocott, Hilary P.; Pinto, Ruxandra; Scales, Damon C.; Achen, Blaine; Brar, Sukhpal; Morrison, Doug; et al.
Editor's Perspective: What We Already Know about This Topic: Major bleeding can occur during cardiac surgery. Although different scoring systems exist, the assessment of bleeding can be variable, and the reliability of these scoring systems has not been determined. What This Article Tells Us That Is New: Two consensus-based scoring systems for assessing bleeding were compared in a substudy of the Transfusion Avoidance in Cardiac Surgery trial. Both the Universal score and European Coronary Artery Bypass Graft scores performed well and may be used as validated outcome measures in future clinical trials. Background: Research into major bleeding during cardiac surgery is challenging due to variability in how it is scored. Two consensus-based clinical scores for major bleeding: the Universal definition of perioperative bleeding and the European Coronary Artery Bypass Graft (E-CABG) bleeding severity grade, were compared in this substudy of the Transfusion Avoidance in Cardiac Surgery (TACS) trial. Methods: As part of TACS, 7, 402 patients underwent cardiac surgery at 12 hospitals from 2014 to 2015. We examined content validity by comparing scored items, construct validity by examining associations with redo and complex procedures, and criterion validity by examining 28-day in-hospital mortality risk across bleeding severity categories. Hierarchical logistic regression models were constructed that incorporated important predictors and categories of bleeding. Results: E-CABG and Universal scores were correlated (Spearman ρ = 0.78, P < 0.0001), but E-CABG classified 910 (12.4%) patients as having more severe bleeding, whereas the Universal score classified 1, 729 (23.8%) as more severe. Higher E-CABG and Universal scores were observed in redo and complex procedures. Increasing E-CABG and Universal scores were associated with increased mortality in unadjusted and adjusted analyses. Regression model discrimination based on predictors of perioperative mortality increased with additional inclusion of the Universal score (c-statistic increase from 0.83 to 0.91) or E-CABG (c-statistic increase from 0.83 to 0.92). When other major postoperative complications were added to these models, the association between Universal or E-CABG bleeding with mortality remained. Conclusions: Although each offers different advantages, both the Universal score and E-CABG performed well in the validity assessments, supporting their use as outcome measures in clinical trials. Abstract : Two consensus-based scoring systems for assessing bleeding were compared in a substudy of the Transfusion Avoidance in Cardiac Surgery trial. Both the Universal score and European Coronary Artery Bypass Graft scores performed well and may be used as validated outcome measures in future clinical trials.Supplemental Digital Content is available in the text.